Percutaneous balloon dilatation of calcific aortic valve stenosis: anatomical and haemodynamic evaluation. Issue 2 (February 1988) - Commeau, P; Grollier, G; Lamy, E; Foucault, J P; Durand, C; Maffei, G; Maiza, D; Khayat, A; Potier, J C
Abstract : Two groups of elderly patients with calcified aortic stenosis were treated by balloon dilatation. In group 1, the valve was dilated just before surgical replacement of the valve. The valvar and annular changes occurring during dilatation were examined visually. In 20 of the 26 patients in this group there was no change. In the six remaining patients mobilisation of friable calcific deposits (1 case), slight tearing of the commissure (4 cases), or tearing of the aortic ring (1 case) were seen. Dilatation did not appear to alter valvar rigidity. In 14 patients (group 2) the haemodynamic gradient across the aortic valve was measured before and immediately after dilatation and one week after the procedure. Dilatation produced an immediate significant decrease of the aortic mean gradient and a significant increase of the aortic valve area. Eight days later the mean gradient had increased and the aortic valve area had decreased. Nevertheless there was a significant difference between the initial gradient and the gradient eight days after dilatation. The initial aortic valve area was also significantly larger than the area eight days after dilatation. The aortic valve gradient rose significantly in the eight days after dilatation and at follow up the gradients were those of severe aortic stenosis.